2013
DOI: 10.1016/j.bpj.2013.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Diastolic Field Stimulation: the Role of Shock Duration in Epicardial Activation and Propagation

Abstract: Detailed knowledge of tissue response to both systolic and diastolic shock is critical for understanding defibrillation. Diastolic field stimulation has been much less studied than systolic stimulation, particularly regarding transient virtual anodes. Here we investigated high-voltage-induced polarization and activation patterns in response to strong diastolic shocks of various durations and of both polarities, and tested the hypothesis that the activation versus shock duration curve contains a local minimum f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…We have studied the effect of the I K1 inward-rectifying potassium current on an anisotropic two dimensional sheet of cardiac tissue using the bidomain model. Experiments reveal little or no hyperpolarization at a virtual anode when a shock is applied to resting tissue [ 6 8 ]. Another experiment showed that hyperpolarization appeared at the beginning of a shock but disappeared within 1 ms [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have studied the effect of the I K1 inward-rectifying potassium current on an anisotropic two dimensional sheet of cardiac tissue using the bidomain model. Experiments reveal little or no hyperpolarization at a virtual anode when a shock is applied to resting tissue [ 6 8 ]. Another experiment showed that hyperpolarization appeared at the beginning of a shock but disappeared within 1 ms [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Experiments in which a stimulus is applied to refractory tissue produce results similar to the predictions of the passive bidomain model, with adjacent regions of depolarization and hyperpolarization [ 3 5 ]. However, when a stimulus is applied to resting (diastolic) tissue, hyperpolarization is rarely seen [ 6 8 ]. One reason for this behavior might be that the shock excited an action potential resulting in active depolarization that masks any hyperpolarization.…”
Section: Introductionmentioning
confidence: 99%